Platelet Inhibition in Acute Coronary Syndrome and Percutaneous Coronary Intervention: Insights from the Past and Present - Gorog, Diana A.; Geisler, Tobias (Thrombosis and haemostasis, 2020)
Abstract Platelet activation and aggregation have a pivotal role in arterial thrombosis and in the pathogenesis of both acute coronary syndromes (ACS) and in the thrombotic complications that occur in patients undergoing percutaneous coronary intervention (PCI). The past 30 years has seen the progress from early trials of clopidogrel and glycoprotein IIb/IIIa inhibitors to the application of more potent P2Y 12 inhibitors prasugrel and ticagrelor. Early enthusiasm for newer and more potent antiplatelet agents, which could reduce ischemic events, has led to the understanding of the importance of bleeding and a desire to individualize and optimize treatment. It has increasingly become apparent that the potency and duration of dual antiplatelet therapy (DAPT) has to reflect the balance between ischemic and bleeding risk. Recently, multiple strategies have been proposed to individualize DAPT intensity and duration to reduce the bleeding and ischemic risks. Strategies of de-escalation of DAPT intensity, as well as shorter (less than a year) or more prolonged (beyond a year) treatment have been proposed, as well as platelet function test and genotype guidance of P2Y 12 inhibitor therapy. Herein, we provide an overview of the progress in the field of antiplatelet therapy for ACS and PCI over the years, showing the current directions of travel. Ongoing studies focusing on personalized antiplatelet treatment will hopefully yield further insight into ways of optimizing outcomes for the individual.